Exploration of the role and mechanism of Rhizoma Paridis total saponins in osteosarcoma based on SPI1/LCN2-mediated ferroptosis - Yang, Ge; Li, Fenghui; Hu, Xiongke; Li, Miao; Liu, Yaoxi; Zhu, Guanghui; Tan, Qian (Frontiers in Oncology, 2025)
BackgroundOsteosarcoma (OS) is a highly aggressive bone malignancy with limited therapeutic options and poor prognosis, particularly in cases of recurrence or metastasis. Recent studies have identified ferroptosis as a promising therapeutic target in OS, with the SPI1/LCN2 regulatory axis emerging as a critical modulator of this process. We hypothesized that Rhizoma Paridis total saponins (RPTS) exert anti-osteosarcoma effects by inducing ferroptosis through inhibition of the SPI1/LCN2 axis.MethodsIn vitro assessments using OS cell lines MG-63 and Saos-2 included cell counting kit-8 (CCK-8) assays for viability, colony formation for proliferation, scratch wound healing for migration, and Transwell chambers for invasion. Ferroptosis markers were evaluated using colorimetric Fe2+ detection, flow cytometric apoptosis analysis, DCFH-DA probes for reactive oxygen species (ROS), DTNB colorimetry for glutathione (GSH) levels, and western blot (WB) for SLC7A11 and GPX4 expression. A subcutaneous xenograft mouse model received OS cell injections for in vivo validation of tumor growth parameters and protein expression. Bioinformatics analysis was conducted to screen OS-specific differentially expressed genes, followed by validation in both in vivo and in vitro experiments using RT-qPCR and WB.ResultsRPTS significantly inhibited OS cell viability, proliferation, migration, and invasion capacity while promoting Fe2+ accumulation and ROS generation. In vivo, RPTS treatment significantly inhibited tumor growth in vivo. Bioinformatics analysis identified LCN2 as the core ferroptosis mediator regulated by upstream transcription factor SPI1. RPTS downregulated SPI1 and LCN2 expression in vitro and in vivo. Both LCN2 overexpression and SPI1 activation reversed RPTS-mediated ferroptosis induction. SPI1 overexpression with LCN2 knockdown attenuated the promoting effect of RPTS on ferroptosis.ConclusionRPTS triggers ferroptosis-mediated OS suppression through SPI1/LCN2 axis inhibition, providing a novel therapeutic strategy to improve clinical outcomes in OS management.